Nightmare themes: an online study of most recent nightmares and childhood nightmares - Schredl, Michael; Göritz, Anja (Journal of clinical sleep medicine, 2018)
Study Objectives:Even though the common diagnostic criteria (ICSD-3, DSM-5) acknowledge that nightmares do not only contain anxiety/fear (definition of the ICD-10) but also other emotions such as grief, disgust, and anger, the definition of a nightmare still focuses on threats to survival, security, or physical integrity. However, empirical studies on nightmare content in larger samples are scarce.Methods:The current study elicited 1,216 of the most recent nightmares including childhood nightmares of a population-based sample.Results:The findings show that nightmares encompass a diversity of different topics, being chased, physical aggression, including death/injury of close persons. Infrequent themes like being the aggressor and suicide are of special interest as they might be related to waking-life psychopathology.Conclusions:The variety of nightmare topics clearly indicate that current definitions of nightmare content are too narrow. Future studies should look into nightmare content of persons in whom nightmare disorder has been diagnosed.Citation:Schredl M, Göritz AS. Nightmare themes: an online study of most recent nightmares and childhood nightmares. J Clin Sleep Med. 2018;14(3):465-471.
Gesehen am 20.04.2020